AQUARIUM MONITORING SYSTEM BASED ON IOT TECHNOLOGY - TERESHCHENKO, ARTEM; PETRUSHAK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The modern development of digital technologies and network solutions has led to rapid progress in the field of the Internet of Things (IoT). IoT integrates various devices that interact with each other via a network to collect, transmit, and analyze data, creating new opportunities for automation, increased efficiency, and convenience in various sectors — from smart homes and cities to industrial equipment and healthcare systems. Thus, IoT is becoming an integral part of modern life.   The relevance of the research lies in the fact that the advancement of IoT technologies opens up broad opportunities for solving important societal and business challenges. However, the implementation of IoT projects requires a thoughtful approach to the selection of hardware platforms, communication protocols, software, and security measures [2]. Considering the rapid development of this field, it is essential to develop innovative solutions that meet modern requirements for efficiency, scalability, and reliability.  The modern development of digital technologies has contributed to the widespread adoption of the Internet of Things (IoT) concept, which allows physical devices to be connected via a network for data exchange and remote control. However, the effective use of such systems requires a combination of optimal hardware, communication protocols, software support, and security measures. The development of small-sized and at the same time functionally powerful solutions for automating household tasks, including aquarium management, is a relevant area of research in the context of a smart environment.  Global practice demonstrates the successful application of IoT in various industries, from medical devices to industrial systems. While large companies use cloud platforms such as AWS IoT or Google Cloud IoT, there is a growing demand for affordable open source solutions (ThingsBoard, Blynk) for educational, household, and research projects. Scientific papers emphasize the importance of choosing the right microcontroller, communication protocol (Wi-Fi, Bluetooth, LPWAN), and power supply circuit. Among the devices often used in IoT projects, the ESP32 stands out due to its balance between price, performance, and energy efficiency.
Keywords: Internet of Things; ESP32; Blynk IoT; automation; sensors; microcontroller